Influence of home-school related factors on students’ schooling attitude towards basic technology in Nigeria - Alade, Ibiwumi Abiodun (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2024)
Students’ readiness to receive what is taught in classroom is a condition of attitude influenced by many factors, and Basic technology in Nigerian junior schools is often affected by many factors. For the subject in schools not to go into extinction therefore, and for the future career prospects embedded in it, this study explored influence of home-school related factors on students’ schooling attitude towards basic technology in Nigeria. Two research hypotheses were tested in the descriptive survey, and 250 junior secondary schools III students were randomly selected in Agege Local Government Area of Lagos State. Students’ Schooling Attitudinal Factors’ Scale (SSAFS) (r = 0.82) was used for data collection while multiple regression statistical tool was used for data analysis. The findings recorded joint (80.8%) and relative influences of home environmental status (0.229, P .05), school facilities (B = 0.227; P .05), peer group (B = 0.215; P .05), teachers’ personality (B = 0.104; P 0.5), and type of school (B = 0.102, P 05) on students’ schooling attitude towards basic technology in junior secondary schools. The results imply that the identified factors among others should be given adequate attention by all stakeholders of education.